Model and Sensor‐Based Recommendation Approaches for In‐Season Nitrogen Management in Corn. (1st November 2015) - Thompson, L. J.; Ferguson, R. B.; Kitchen, N.; Frazen, D. W.; Mamo, M.; Yang, H.; Schepers, J. S.
Abstract : Nitrogen management for corn ( Zea mays L.) may be improved by applying a portion of N in‐season. This investigation was conducted to evaluate crop modeling (Maize‐N) and active crop canopy sensing approaches for recommending in‐season N fertilizer rates. These approaches were evaluated during 2012–2013 on 11 field sites, in Missouri, Nebraska, and North Dakota. Nitrogen management also included a no‐N treatment (check) and a non‐limiting N reference (all at planting). Nitrogen management treatments were assessed for two hybrids and at low and high seeding rates, arranged in a randomized complete block design. In 9 of 11 site‐years, the sensor‐based approach recommended lower in‐season N rates than the model (collectively 59% less N), resulting in trends of higher partial factor productivity of nitrogen (PFPN ) and higher agronomic efficiency (AE) than the model. However, yield was better protected by the model‐based approach. In some situations, canopy sensing excelled at optimizing the N rate for localized conditions. With abnormally warm and moist soil conditions for the 2012 Nebraska sites and presumed high levels of inorganic N from mineralization, N application was appropriately reduced, resulting in no yield decrease and N savings compared to the non‐limiting N reference. Depending on the site, both recommendation approaches were successful; a combination of model and sensor information may optimize in‐season decision support for N recommendation.